Hubungan Tingkat Pengetahuan Dengan Tindakan Kesehatan Rambut Pada Pengemudi Ojek Online di Gubeng - Tasya Aisyah Ramadani; Biyan Yesi Wilujeng; Sri Dwiyanti; Octaverina Kecvara Pritasari (Jurnal Tata Rias, 2026)
Hair health is an essential aspect of personal hygiene, particularly for online motorcycle taxi drivers who are frequently exposed to pollution, dust, and prolonged helmet use. This research aimed to assess the level of hair health knowledge, hair care practices, and the relationship between the two among online motorcycle taxi drivers in Gubeng, Surabaya. a quantitative correlational design was applied. 50 drivers in were selected using purposive sampling and data were collected through questionnaires. The data were analyzed using the Pearson Product Moment correlation test. The findings showed that the most participants had good knowledge, while hair health practices varied. The correlation coefficient (r= 0,577; p < 0,05) indicated a significant positive relationship between knowledge and hair health practices. Higher knowledge levels were associated with better hair health practices.Keywords: Knowledge, Hair Health, Online Motorcycle Taxi Driver, Gubeng.